Identifikasi Kebutuhan untuk Pengembangan Game Edukasi tentang Pengolahan Benih Kacang Hijau bagi Siswa Sekolah Dasar - Elya Fitriani; Roemintoyo Roemintoyo; Sarwanto Sarwanto (Journal on Education, 2023)
Research on educational games for managing green bean seeds is important because it can increase children's understanding of agriculture, ecosystems and environmental responsibility. This also supports the development of ecological awareness from an early age and encourages future generations to care more about nature. Therefore, this research aims to identify the need for educational games that can facilitate students learning to manage green bean seeds. The research method is mixed research. The data collected is in the form of quantitative and qualitative data. Quantitative data collection techniques through giving questionnaires to 19 elementary school students. Qualitative data was obtained from observations of learning activities with the research subject, namely Grade 5 teachers. Quantitative data was analyzed through descriptive analysis with percentages, and qualitative data was analyzed using the Bogdan and Biklen model. The results of the analysis of observation activities during learning show that teachers still dominate material delivery activities, and rarely use digital learning media because they are limited to text-based learning media. This is also reinforced by student questionnaire responses which show that the majority of students are familiar with using Android smartphones. However, their smartphone use is mostly for entertainment such as watching YouTube and playing games, not for learning purposes. From the results of this research, it is clear that there are opportunities for developing educational games because students prefer to use smartphones to access games. Furthermore, most of them expressed interest in using this educational game so they could learn the material at home.